Optimal scheduling of supercritical coal-fired power plant integrated with CO2 capture process considering solvent storage. Issue 9 (2022) - Qiu, Ruohan; Xi, Han; Wu, Xiao
Abstract: The deployment of lean/rich solvent storage devices within the solvent-based carbon capture process provides an effective way to upgrade the flexibility of the integrated power plant-CO2 capture process, especially in the scenarios with strict carbon emission requirements. This paper provides an optimal scheduling strategy to fully exploit the roles of solvent storage within the supercritical coal-fired power plant integrated with CO2 capture process, so that the net operating profits of the plant can be maximized. System economy, capacity of carbon emission reduction and operating flexibility are then analyzed through comparison with the same system without using the solvent storage equipment under two different operating modes. The results show that the system considering solvent storage has outstanding economic advantages: it can achieve better carbon emission reduction performance under the flexible carbon capture level mode; and can greatly improve the flexibility in power generation under the fixed carbon capture level mode.